Iran's Dual Diplomacy During the Dhofar Movement (1965-1975) - Ebrahiminejad, Badrjahan; Salehi Amiri, Reza; Sharafi, Mahboube; Forouzesh, Sina (Historical Study of War, 2024)
The Dhofar movement which lasted for ten years was initially influenced by Arabian nationalism led by Jamal Abdul Nasser, but shifted towards the Eastern bloc after the Arabs’ defeat by Israel (1967 AD). Shortly before England’s withdrawal from Persian Gulf when Sultan Qaboos entered Oman’s political scene (1970 AD), Iran suppressed the movement with support of England and America. The influences of Arabian nationalism and communism current were the two major challenges during this decade shaping Iran’s political response to the movement. Iran implicitly declared neutrality to the movement despite confirming legitimacy of its religious leader. However, with arrival of Sultan Qaboos, Iran directly participated in its suppression, and the main subject of this paper is to know why. Findings represent that the above-mentioned challenges significantly impacted on Iran’s adoption of two distinct political approaches. While affirming legitimacy of Sultan’s adversaries, Iran first avoided bolstering the movement’s position against the West and maintained positive neutrality and refrained from any actions. Later on, to consolidate Sultan Qaboos authority and to confront the growing influence of the East, Iran suppressed the movement. This article is compiled using a historical method and is written with a descriptive analytical approach.
Keywords: Dhofar; Relations -- Oman -- Iran